Exploring the impact of automation on employment during expansions and contractions: An examination of Okun's Law. - Brzozowski, Michał; Siwińska-Gorzelak, Joanna (International Labour Review, 2025)
This article investigates the impact of automation, specifically robotization, on the short-term relationship between employment and output as described by Okun’s Law, using panel data from 35 OECD countries between 1996 and 2020. The study finds that increased robot intensity mitigates rises in unemployment and reduces job losses during economic contractions, thereby contributing to job-preserving recessions. However, robotization does not significantly affect employment responsiveness during economic expansions, providing no evidence that automation causes jobless recoveries. These findings are robust across multiple econometric methods, specifications of Okun’s Law, and after controlling for labor market institutions such as employment protection legislation. The results suggest that the degree of robotization influences how fiscal and monetary policies impact employment stability over the business cycle.